2014
DOI: 10.1111/jvp.12181
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intravenous and subcutaneous cefovecin in alpacas

Abstract: The purpose of this study was to determine the pharmacokinetics of cefovecin after intravenous and subcutaneous dose of 8 mg/kg to alpacas. Bacterial infections requiring long-term antibiotic therapy such as neonatal bacteremia, pneumonia, peritonitis, dental, and uterine infections are a significant cause of morbidity and mortality in this species. However, few antimicrobials have been evaluated and proven to have favorable pharmacokinetics for therapeutic use. Most antimicrobials that are currently used requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…29,30 It has been reported that the actual observed unbound proportions of various β-lactam antibiotics can be highly variable in ill people. 3,4 This current study and several others demonstrate a wide interspecies PPB variance, such as 69-91% in alpacas, 9 37.9-50.2% in Hermann's tortoises 13 and 78% in sea otters. 32 It is also important to recognise that high PPB is not indicative of a long elimination half-life; PPB is just one of many factors that may influence drug disposition.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…29,30 It has been reported that the actual observed unbound proportions of various β-lactam antibiotics can be highly variable in ill people. 3,4 This current study and several others demonstrate a wide interspecies PPB variance, such as 69-91% in alpacas, 9 37.9-50.2% in Hermann's tortoises 13 and 78% in sea otters. 32 It is also important to recognise that high PPB is not indicative of a long elimination half-life; PPB is just one of many factors that may influence drug disposition.…”
Section: Discussionsupporting
confidence: 74%
“…33 Cefovecin has been demonstrated to have a slow elimination in the cat and dog because it combines high protein binding with a relatively low clearance. 3,4 This current study and several others demonstrate a wide interspecies PPB variance, such as 69-91% in alpacas, 9 37.9-50.2% in Hermann's tortoises 13 and 78% in sea otters. 12 Likewise, the cefovecin elimination rate has been shown to be more variable across species, with the half-life ranging from 136 AE 12 h in the dog to 8.5 AE 0.78 h in baboons.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Some authors have attributed this property to the highly plasma protein binding that some domestic animals presented (e.g., 96–98.7% in dogs (Stegemann et al ., ) and >99% in cats (Stegemann et al ., )), and because only the free drug is eliminated mainly via the kidneys (EMEA, ). However, herbivores and some exotic animals have not reached the same therapeutic duration, having a much shorter half‐life in all the species that were investigated, independently of their antibiotic‐plasmatic protein binding (Thuesen et al ., ; Bertelsen et al ., ; Gilabert et al ., ; Montesinos et al ., ; Papp et al ., ; Cox et al ., ). Because of being impossible to emulate a similar dosing scheme as the ones proposed for dogs and cats, no studies of cefovecin in horses have been published.…”
Section: Introductionmentioning
confidence: 97%